Multisensory Approach in Reog Ponorogo Arts Education for Holistic Early Childhood Development - Arisanti, Fifi; Sugianto, Alip; Setiawan, Wahyudi (Jurnal Borneo Administrator, 2026)
This study is grounded in the urgency of preserving local wisdom within early childhood education and the need to integrate traditional culture with national educational policies, particularly in the context of the Merdeka Curriculum. The purpose of this research is to examine the application of a multisensory approach in Reog Ponorogo arts education as a medium for promoting holistic early childhood development aligned with local cultural values and national goals. This research employed a descriptive qualitative method, specifically investigating children's authentic learning experiences through in-depth observations, open interviews, and documentation of learning activities. The findings reveal that integrating a multisensory approach in Reog learning through movement, music, costumes, and folklore has a positive impact across multiple developmental domains. Notably, improvements were observed in sensory-motor coordination, such as enhanced body balance during dance imitation and rhythm synchronization while responding to Reog’s musical patterns. Cognitive development was stimulated through cultural symbol recognition and narrative sequencing, while social-emotional skills were nurtured through collaboration in performances and increased cultural pride. In conclusion, the implementation of a multisensory approach in Reog Ponorogo arts not only supports holistic early childhood development but also serves as a bridge between local wisdom and national policy in contextualized educational practices. This study implies the importance of culturally based education in the implementation of the Merdeka Curriculum in early childhood institutions.